An analysis of classroom management challenges to the novice elementary school teachers in Islamabad, Pakistan (Journal of Humanities, Social and Management Sciences (JHSMS-Asia), 2024)
This study analysed the classroom management challenges faced by novice Elementary School Teachers (ESTs) who joined the Federal Directorate of Education (FDE), Islamabad, in 2022. The physical, administrative and individual challenges of the classroom were studied. Using a quantitative approach, the research focused on 661 ESTs, consisting of 249 males and 412 females. A stratified sample of 248 teachers (95 males, 153 females) was selected, and data were collected via a self-developed questionnaire. Experts confirmed the instrument’s validity and reliability were measured with a Cronbach’s alpha of 0.885. Data analysis revealed that novice teachers face several challenges, including limited classroom space, insufficient furniture, and inadequate resources for science labs. They also face challenges in maintaining discipline, disruptive behaviour, and irrelevant questions from students. Furthermore, individual differences among students due to varying IQ levels, learning interests, and socio-economic backgrounds proved challenging. Overcrowded classrooms hinder novice teachers' ability to focus and provide individual attention. The study concluded that heads of educational institutions must offer consistent guidance and support to newly appointed ESTs, especially during their first year, to improve classroom management skills.